Zouglou Visions of Transitional Justice. (4th May 2022) - Kouadio, Lyn J -V
ABSTRACT ∞ : This article argues that through Zouglou music, Ivorian youths have defined what it means to deliver justice in the wake of violence by positioning Zouglou and Zouglou-Nouchi "ways of being" as an inescapable means of political legitimation. Beginning with the turn from Houphouët's single party rule to multiparty politics in 1990, to the 2002–2007 and 2010–2011 eras of violent conflict, Zouglou artists, themselves youths, have shaped the terms of democratic transition. They have crafted a space wherein to discuss the meanings of violent conflict and justice as well as opened possibilities for youths to shape what the Ivorian democratic future should be. In doing so, youths have prescribed new ways of political legitimation. As a result, in Côte d'Ivoire politicians do not only vie for the presidential seat but also engage with Zouglou and Zouglou-Nouchi "ways of being" to gain popular affection.